1988
DOI: 10.1002/bem.2250090207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static magnetic fields on diffusion in solutions

Abstract: Static magnetic fields affect the diffusion of biological particles in solutions through the Lorentz force and Maxwell stress. These effects were analyzed theoretically to estimate the threshold field strength for these effects. Our results show that the Lorentz force suppresses the diffusion of charged particles such as Na+, K+, Ca2+, Cl-, and plasma proteins. However, the threshold is so high, i.e., more than 10(4) T, that the Lorentz force does not affect the ion diffusion at typical field strengths (a few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…However, the results presented in39 show that in solution, the Lorentz force can suppress the diffusion of univalent ions (e.g., Na + , K + , and Cl − ), but the threshold magnetic field is extremely high, approximately 5.7 · 10 6  T (which is 2–4 orders of magnitude less than the magnetic field at a magnetar). On the other hand, the theoretically predicted threshold of gradient fields for producing a change in ion diffusion through the magnetic gradient stress is more than 10 5  T 2 m −1 for paramagnetic molecules FeCl 3 and 0 2 and plasma proteins39. Thus, in low and moderate magnetic fields, the biological effects should be rather dependent on the magnitude of the magnetic field gradient and not on the strength of the magnetic field, as was recently demonstrated in experiments with THP-1 cells32.…”
Section: Resultsmentioning
confidence: 91%
“…However, the results presented in39 show that in solution, the Lorentz force can suppress the diffusion of univalent ions (e.g., Na + , K + , and Cl − ), but the threshold magnetic field is extremely high, approximately 5.7 · 10 6  T (which is 2–4 orders of magnitude less than the magnetic field at a magnetar). On the other hand, the theoretically predicted threshold of gradient fields for producing a change in ion diffusion through the magnetic gradient stress is more than 10 5  T 2 m −1 for paramagnetic molecules FeCl 3 and 0 2 and plasma proteins39. Thus, in low and moderate magnetic fields, the biological effects should be rather dependent on the magnitude of the magnetic field gradient and not on the strength of the magnetic field, as was recently demonstrated in experiments with THP-1 cells32.…”
Section: Resultsmentioning
confidence: 91%
“…For long time [Kinouchi et al, 1988;Chiabrera et al, 1992] it has been debated whether the energy associated with weak electromagnetic fields is enough to supply the energy requested by the changes that have been ascribed to the fields. The results illustrated in this study have shown that the EM-ELF field are acting at the interface between the liquid SBF and the air, and the experimental measurements of the SBF surface tensions will allow investigation of whether or not the energy balance is obeyed.…”
Section: Spontaneous Processes Under Em-elf Exposurementioning
confidence: 99%
“…[10] Thus, the presence of an HGMF alters the ion flux balance across the cell membrane, thereby changing the membrane potential. However, the results presented in previous work [55] show that in solution, the Lorentz force can suppress the diffusion of univalent ions (e.g., Na þ , K þ , and Cl À ), but the threshold magnetic field is extremely high, approximately 5.7 Á 10 6 T (which is 2-4 orders of magnitude less than the magnetic field at a magnetar). [10] Static homogeneous magnetic fields can also affect the diffusion of biological particles through the Lorentz force and hypothetically change the membrane potential.…”
Section: Membrane Potentialmentioning
confidence: 85%
“…By deriving a generalized form for the Nernst equation, it was shown that an externally applied magnetic field with a spatial gradient value on the order of 10 8 -10 9 Tm À1 can directly change the cell membrane potential by 10 mV due to magnetic gradient forces regulating the entry of sodium, potassium, and calcium ions and biologically relevant molecules. [55] However, the results presented in previous work [55] show that in solution, the Lorentz force can suppress the diffusion of univalent ions (e.g., Na þ , K þ , and Cl À ), but the threshold magnetic field is extremely high, approximately 5.7 Á 10 6 T (which is 2-4 orders of magnitude less than the magnetic field at a magnetar).…”
Section: Membrane Potentialmentioning
confidence: 93%
See 1 more Smart Citation